Non Financial Reporting between Necessity and Obligation - GÂDĂU, Liana (Journal of Advanced Research in Management, 2017)
Currently the focus is on the fact that non-financial reporting is essential for the transition to a sustainable economy which combines long-term profitability with social inclusion and protection of natural resources. It aims is to increase the transparency and comparability among large companies. The information they provide will be available direct investors interested in sustainable development of target companies, investors can have a complete image on the position and performance not only in economic and financial matters but also in aspects of sustainable development.